Smile Attractiveness: Perspectives of Dental and Non-Professional Students - Yunus Emre Bedir; Hikmetnur Danışman (Current Research in Dental Sciences, 2025)
Objective: The aim of this study is to investigate the perception of smile attractiveness among dental students and non-specialist individuals, with the aim of drawing attention to their views on smiling.Methods: Frontal smile photographs of a woman who underwent orthodontic treatment were modified to create 12 new smile photographs, and these smiles were evaluated by two different groups in terms of buccal corridor width, midline deviation, smile arc, and occlusal cant. Overall, 256 evaluators from two groups (Group 1=dental students, Group 2=non-professional students) rated these modified photographs of different smiles of the same individual for attractiveness using a visual analog scale (VAS).Results: In both groups, the unmodified reference photo had the highest attractiveness score. Dental students and non-professionals significantly differ in perceiving midline shifts (p